2010
DOI: 10.1111/j.1439-0418.2010.01587.x
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal and feeding deterrent activities of essential oils in the cabbage looper, Trichoplusia ni (Lepidoptera: Noctuidae)

Abstract: Ten essential oils were tested against the cabbage looper, Trichoplusia ni larvae for contact, residual and fumigant toxicities and feeding deterrent effects. Against third instar T. ni, Syzygium aromaticum (LD50 = 47.8 μg/larva), Thymus vulgaris (LD50 = 52.0 μg/larva) (the two positive controls) and Cinnamomum glanduliferum (LD50 = 76.0 μg/larva) were the most toxic via topical application. Litsea pungens (LD50 = 87.1 μg/larva), Ilex purpurea (LD50 = 94.0 μg/larva), Cinnamomum cassia (LD50 = 101.5 μg/larva) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 36 publications
2
24
0
6
Order By: Relevance
“…However, mean per cent FDI was not differed significantly between the interactions of essential oils and concentrations (F 135, 8 = 0.64; p > 0.05). The present results supported by Jiang et al (2012) who reported the essential oils of Cymbopogon citratus, C. nardus and C. cassia showed strong feeding deterrent against larvae of Trichoplusia ni. Similarly, asarones isolated from the essential oil of A. calamus rhizomes also showed antifeedant to Peridroma saucia (Koul et al 1990).…”
Section: Feeding Deterrent Activity Of Essential Oilssupporting
confidence: 94%
See 1 more Smart Citation
“…However, mean per cent FDI was not differed significantly between the interactions of essential oils and concentrations (F 135, 8 = 0.64; p > 0.05). The present results supported by Jiang et al (2012) who reported the essential oils of Cymbopogon citratus, C. nardus and C. cassia showed strong feeding deterrent against larvae of Trichoplusia ni. Similarly, asarones isolated from the essential oil of A. calamus rhizomes also showed antifeedant to Peridroma saucia (Koul et al 1990).…”
Section: Feeding Deterrent Activity Of Essential Oilssupporting
confidence: 94%
“…Besides, essential oils are potentially suitable for integrated pest management programmes. Insecticidal activity of essential oils has been reported against cabbage looper, Trichoplusia ni (Jiang et al 2012), armyworm, Pseudaletia unipuncta (Akhtar et al 2008) and stored product pests (Dales 1996). Intensive use of chemical insecticides for the control of Plutella xylostella has led to this pest developing resistance to a wide range of insecticides and caused serious damage to natural enemies (Ke et al 1991;Talekar & Shelton 1993).…”
Section: Introductionmentioning
confidence: 98%
“…Variations in chemical composition owing to seasonal or geographic differences, growth conditions, and extraction methods for thyme (Thymus vulgaris L.) essential oil (Senatore 1996;Hudaib et al 2002;Asllani and Toska 2003) and lemongrass (Cymbopogon citratus Stapf.) essential oil (Zheljazkov et al 2011;Desai et al 2014;Moncada et al 2014) are well documented, along with their insecticidal activity (Lee et al 2001;Machial et al 2010;Jiang et al 2012), repellence (Diaz-Montano andTrumble 2013;Zhang et al 2013), and physiological impact such as insect larval growth or feeding deterrence (Hummelbrunner and Isman 2001;Jiang et al 2012) as well as acaricidal activity (Sertkaya et al 2010). Although many screening data highlighted the merit of both essential oils as insect control agents, understandings of the activities of individual constituents and their comparative contributions to the overall toxicity are vital in the considerations of candidate oils as for practical use (i.e., determinations of cultivation condition, commercialization, or quality control).…”
Section: Introductionmentioning
confidence: 98%
“…Estos AEs son mezclas muy complejas, alrededor de 50 compuestos, de monoterpenos, sesquiterpenos, aldehídos, cetonas y fenoles (Isman et al, 2010). Los monoterpenos son las moléculas más abundantes, llegando a representar hasta el 90% del aceite (Thripathi et al, 2009).…”
Section: Perfil Químico Y Biológico De Aceites Esenciales De Plantas unclassified
“…Por ello, resulta muy complicado establecer relaciones estructura-actividad al no poder correlacionar la actividad encontrada con los componentes mayoritarios del aceite. Este comportamiento ha sido descrito en la actividad antialimentaria de aceites esenciales de Lavandula luisieri Rozeira (Gonzá-lez-Coloma et al, 2011) y T. vulgaris (Jiang et al, 2010) así como en el estudio de la actividad tóxica y antialimentaria de 12 monoterpenos presentes en la composición de la mayoría de los aceites esenciales (Hummelbrunner e Isman, 2001). En este sentido, se ha corroborado que la combinación de p-cimeno + carvacrol es capaz de aumentar 8 veces la actividad tóxica fumigante frente a S. littoralis cuando se compara la actividad de la mezcla con la de los componentes individuales (Pavela, 2010).…”
Section: Actividad Antialimentariaunclassified